THE INDUCE DAMAGE TO LIVER AND KIDNEY OF WISTAR RAT BY SPENT VEGETABLE OIL AND THE AMELIORATING POTENTIALS OF COCONUT OIL - Simon, Istifanus Adamun; Solomon, Maryam D.; Sangodare, Rose S.A.; Dabak, Jonathan D.; Abdullahi, Abubakar; Abdulkadir, Jibrin (NUTRITURE JOURNAL, 2025)
It has been a regular practice in this part of the world to continually use spent edible oil and consumed it without knowing the harmful effects of such. Heating results in the formation of free reactive oxygen species (ROS) which is responsible for oxidative stress and changes to various organs in the body. The study aimed at investigating the changes caused on liver and kidney by consumption of repeatedly used (spent) oil and possible ameliorating potential of virgin coconut oil (VCO) on spent vegetable oil-induced liver and kidney changes in Wistar albino rats. Blood samples were obtained and assayed for biomarkers of liver and kidney damage; It was observed that spent vegetable oils induced severe damage on liver and kidney. While administration of virgin coconut oil significantly (p<0.05) reversed the changes induced by the spent oil as observed in the biomarkers AST, ALT, ALP, Urea, Creatinine, Uric acid, Total serum protein, Albumin. These findings suggest that VCO could ameliorate the adverse effect of consumption of spent oil on liver and kidney indices in rats.